The leadership and role of Sabah Muslim women in various dimensions of life - Saifulazry Mokhtar; Irma Wani Othman; Kasoma Thia; Romzi Ationg; Mohd Azri Ibrahim; Mohd Khairi Lebai Ahmad (Human Resource Management Academic Research Society (HRMARS), 2025)
There is no denying that women have a huge role in the history of Islam. The glorious history of Muslims has shown how women have such a noble and high position in society. According to the Islamic perspective, the role of women and men is the same where they have responsibilities that need to be fulfilled before Allah SWT whether in special worship or general worship. Thus, this study aims to look at the roles and responsibilities of women especially in the family and society, as well as the role of women in politics in Sabah. This study uses the method of document analysis study which refers to the interpretation of the Quran and snippets of hadiths as well as past studies related to the role and responsibilities of women in Islam as well as their involvement in politics. The results of this study found that Islam did not prevent the people of Eve from engaging in any work except in matters reserved for the people of Adam to lead it. However, in the political aspect the role of the woman is permissible if their roles and responsibilities as a wife and mother are not neglected. Islam suggested that the people of Eve be more concerned and priorities the responsibility of being a wife in safeguarding the harmony of the household and would be able to produce a civil society in line with the religious requirements.